Historical logic and maritime cultural foundation of China’s initiative of building a maritime community with a shared future - Zhu, Xiong; Mao, Zhengkai; Qu, Jinliang; Zhang, Zhijun (Frontiers in Marine Science, 2024)
Building a “Maritime Community with a Shared Future” (MCSF) is a maritime development concept with Chinese characteristics proposed by Chinese President Xi Jinping in 2019. It is based on the rich cultural tradition and unique historical value of China’s maritime civilization. It aims to solve real ocean problems and has outlined the future direction of human ocean development from the perspective of China. The essence of the MCSF is an issue of both ocean cultural and development concepts. It is a conceptual issue that transcends specific national boundaries and regions and is based on how all of humankind, with common interests and common values, can develop in harmony with the oceans. It is not a covert discourse strategy adopted by China in order to realize its “maritime power” ambition, as occasionally described by some Western countries. Starting with an analysis of the essential nature and implications of maritime culture by Chinese researchers, this article clarifies and summarizes the interaction, exchange, and integration of Chinese maritime culture in East Asia from a historical perspective, and extracts the unique characteristics and values of Chinese maritime culture. From the perspective of human–sea interactions, the three historical stages, as well as the existing problems of transforming and upgrading human–ocean culture, are analyzed. The article also contrasts Chinese and Western maritime cultures and proposes to absorb the outstanding achievements of both Chinese and Western maritime civilizations into a common framework in order to fundamentally reverse the antagonistic human–sea relationship that has existed historically. Finally, we propose giving full play to the fundamental role of marine cultural exchange and integration and, through international cooperation on specific issues in the field of global ocean international relations, propose specific and feasible practical pathways to promoting the realization of the MCSF.